PENETAPAN RENDEMEN EKSTRAK DAUN JAMBU MAWAR (Syzygium jambos L. Alston) BERDASARKAN VARIASI KONSENTRASI ETANOL DENGAN METODE MASERASI - Syamsul, Eka Siswanto; Anugerah, Olanda; Supriningrum, Risa (Jurnal Riset Kefarmasian Indonesia, 2020)
Syzygium jambos is a medicinal plant. This study aims to determine the effect of variations in ethanol concentration on yield of guava leaf extract by maceration method. The research conducted was experimental research. The research phase includes sample collection, determination, manufacture of simplicia, extraction by maceration with variations in ethanol concentration, determination of yield, phytochemical screening and determination of drying losses. Phytochemical screening results showed that 50% of ethanol extracts of positive rose guava contained flavonoids, tannins, saponins and steroids / terpenoids, 70% ethanol and 90% positives contained flavonoids, tannins and steroids / terpenoids. The yield of rose guava ethanol extract was 50% (23.01% ± 0.372), 70% ethanol (21.96% ± 1.181) and 90% ethanol (16.57% ± 0.384). LSD test results showed a significant difference (p <0.05) between the 90% to 50% and 70% groups.